Long-term investigations on ammonium removal with zeolite in compact vertical flow treatment wetlands under field conditions. (25th January 2022) - Ruiz-Ocampo, Hernán; Tondera, Katharina; Paing, Joëlle; Molle, Pascal; Chazarenc, Florent
Abstract: The scope of this study was to investigate if using zeolite as a reactive material in a vertical-flow wetland under field conditions improves ammonium removal from domestic wastewater in the long term. The experimental setup consisted of two pilot-scale first stage French vertical flow treatment wetlands (2.3 m 2 surface area each), which were implemented under field scale conditions inside a wastewater treatment plant in the central region of France (L'Encloitre, 37360). The filters were operated during 27 months. A compact pilot containing Leca ® as a main filtration layer (Ø 1–5 mm) was compared to a similar one filled with natural zeolite (Ø 2–5 mm). The pilots were fed according to regular feeding/resting periods (3½/7 days) and the nominal loading rate was of 300 g COD m −2 d −1 and 33 g·N·m −2 ·d −1 during operation. In both pilots, results showed a removal efficiency of more than 90 and 85% for TSS and COD, respectively. They also showed an increased NH4 -N removal of 9% on average (total removal efficiency of 84%) with the use of zeolite compared to Leca ® . The ion exchange capacity of zeolite seemed not to be affected after 27 months of experiments; however, the material was compacted and more friable after operation. HIGHLIGHTS: A zeolite layer in a French Vertical-Flow Wetland improved the ammonium removal. Seasonal effects impacted the removal efficiency. Material compaction of the zeolite during the trial period needs to be further investigated.